2012
DOI: 10.1177/0013916512466094
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Beyond Your Visual Field

Abstract: Previous research has suggested that the layout of urban spaces can have a substantial influence on how people navigate through those spaces. However, to date, few studies have directly investigated how changes in layout interact with changes in visual field to shape a person's route choice. Across two experiments, the influence of visual field and spatial layout was manipulated using virtual reality. It was found that route choice was significantly influenced by the configuration of a space-The more consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Moreover, complex topology has been associated with reduced visual sampling in older patients with Parkinson’s Disease, when navigating environments with turning points rather than straight paths (Galna et al, 2012). In line with this evidence, Barton et al (2014) found impaired navigation skills (measured in terms of speed and accuracy in reaching a target) in environments with low intelligibility, which they operationalized as the correlation of connectivity (the number of potential routes connected to a specific path in a network) and integration (the average number of turns required to change path in the network). The results were independent of familiarity with the environment or accessibility to visual information.…”
Section: Complexity and Cognitive Performancementioning
confidence: 77%
“…Moreover, complex topology has been associated with reduced visual sampling in older patients with Parkinson’s Disease, when navigating environments with turning points rather than straight paths (Galna et al, 2012). In line with this evidence, Barton et al (2014) found impaired navigation skills (measured in terms of speed and accuracy in reaching a target) in environments with low intelligibility, which they operationalized as the correlation of connectivity (the number of potential routes connected to a specific path in a network) and integration (the average number of turns required to change path in the network). The results were independent of familiarity with the environment or accessibility to visual information.…”
Section: Complexity and Cognitive Performancementioning
confidence: 77%
“…This could be interpreted as inadequacy of Space Syntax to cover complex multiparametric settings—especially as Space Syntax takes a minimal number of parameters into account—but also could mean that psychiatric facilities are still what Goffman named “total institutions” [79]. At the same time, it highlights considerable limitations of Space Syntax algorithms when it comes to healthcare facilities [80–82] or when the research population is not normative [83, 84].…”
Section: Discussionmentioning
confidence: 99%
“…Space Syntax is an architectural analytic tool that has been leveraged not only by architects, but also by other scientists (including cognitive scientists, psychologists, and geographers) to investigate the relationship between properties of space and human behavior in it (Barton, Valtchanov & Ellard, 2014;Dalton, Hölscher & Turner, 2012;Emo, Al-Sayed & Varoudis, 2016;Hillier & Hanson, 1984;Hillier & Vaughan, 2007;Kim & Penn, 2004;Li & Klippel, 2016;Nubani & Wineman, 2005;Penn, 2003;Peponis, Ross & Rashid, 1997). In the present study, we examine how well measures derived from two popular Space Syntax techniques-the Axial Map Analysis and the Visibility Graph Analysis (VGA)predict performance in spatial memory tasks following navigation of a virtual environment.…”
mentioning
confidence: 99%